What is the impact of drug therapy with antiresorptive agents on the success of dental implants? a literature review (Research, Society and Development, 2021)
Objective: To review the current literature and provide the latest information on anti-resorptive agent-induced osteonecrosis of the jaw (ARONJ), including our basic and clinical research findings, as well as discuss the risks of developing osteonecrosis in patients undergoing dental implant surgery in use of anti-resorptive drugs (ARDs). Methods: A literature review was performed using articles published in indexed journals based on Pubmed, Web of Science, Embase and Scopus databases. Results: Our results show that the placement of dental implants in patients treated with ARDs should be carefully evaluated, these patients are not free from complications and, therefore, the risk assessment should be done individually, as one of the most serious complications, although rare, is the ARONJ. Conclusion: Thus, all patients treated with this type of drug should be informed about the risk of implant loss or the possibility of osteonecrosis, being necessary to inform about the increased risk also patients who already have osteointegrated implants and will start therapy with bisphosphonates (BPT). And, in addition, establishing a relationship and collaboration between doctor, dentist and patient is essential for the good prognosis of these cases.